Industrial and agricultural ammonia point sources exposed. (6th December 2018) - Van Damme, Martin; Clarisse, Lieven; Whitburn, Simon; Hadji-Lazaro, Juliette; Hurtmans, Daniel; Clerbaux, Cathy; Coheur, Pierre-François
Abstract Through its important role in the formation of particulate matter, atmospheric ammonia affects air quality and has implications for human health and life expectancy1, 2 . Excess ammonia in the environment also contributes to the acidification and eutrophication of ecosystems3–5 and to climate change6 . Anthropogenic emissions dominate natural ones and mostly originate from agricultural, domestic and industrial activities7 . However, the total ammonia budget and the attribution of emissions to specific sources remain highly uncertain across different spatial scales7–9 . Here we identify, categorize and quantify the world's ammonia emission hotspots using a high-resolution map of atmospheric ammonia obtained from almost a decade of daily IASI satellite observations. We report 248 hotspots with diameters smaller than 50 kilometres, which we associate with either a single point source or a cluster of agricultural and industrial point sources—with the exception of one hotspot, which can be traced back to a natural source. The state-of-the-art EDGAR emission inventory10 mostly agrees with satellite-derived emission fluxes within a factor of three for larger regions. However, it does not adequately represent the majority of point sources that we identified and underestimates the emissions of two-thirds of them by at least one order of magnitude. Industrial emitters in particular are often found to be displaced or missing. Our results suggest that it is necessary to completely revisit the emission inventories of anthropogenic ammonia sources and to account for the rapid evolution of such sources over time. This will lead to better health and environmental impact assessments of atmospheric ammonia and the implementation of suitable nitrogen management strategies. Satellite observations reveal over 200 ammonia hotspots associated with agricultural and industrial point sources, which emit much larger quantities of ammonia to the atmosphere than previously thought.